Violence in Martin McDonagh's The Pillowman - Abdulhasan Ali, Basma; Atallah Diyaiy, Sabah (Al-Adab Journal, 2021)
The 1990s have been of utmost importance for Ireland and the Irish as this decade is characterised by a great diversity of problems: economic problems, unemployment and migration which came as a result of these problems, racial harassment experienced abroad, psychological problems, the Troubles whose serious impact was felt not only in Northern Ireland but also in the Republic of Ireland, which emerged as a consequence of the conflict between the Catholics and the Protestants because of the political status of Northern Ireland and which began at the end of the 1960s and ended in 1998 with Belfast Agreement; self-centeredness emerging as a repercussion of the Celtic Tiger period which was witnessed between 1995 and 2000 and which means economic development in Ireland, and, lastly, the problem of violence. Martin McDonagh, anAnglo-Irish playwright represents these problems emphasising the problem of violence encountered in this decade in a satirical but grotesque way particularly in The Pillowman.